The Brazilian engineering modernization with the integrated master’s degree model 3 + 2 / A modernização da engenharia Brasileira com o mestrado integrado modelo 3 + 2 - Neto, Vicente Machado (2018)
Many studies have been done aiming atcurriculums models of Engineering Courses in Brazil. In the search for a model it is necessary to dare, to became them compatible with international reality. The purpose of this article is to present a model suitable to the international education community that complies with Brazilian legislation. The model also helps the creation of innovative Engineering Courses, between areas of knowledge and it promotesgreater Courses integration with the labor market and graduate programs. The methodology used in this article to arrive at anEngineering Course model that may be appropriate to the Brazilian reality was initially based on an extensive research of the Engineering Courses offered worldwide. Due to the research, the authors' experience and the Brazilian reality, some important conditions were detected to verify the adequacy of the proposed model.After the model introduction there were general discussions on several topics to reach the quality in education.Concluding, the University is no more the only source of society knowledge.It’s necessary models that can include in harmony new sources of knowledge, outside the University environment, inside the Engineering Courses.The current models and the departmentalized University structure do not answer to innovative Engineering Courses. Finally, it's must recognize that Brazilians Engineering Courses are in disagreement with what is practiced internationally.